The HUBUNGAN PERAN ORANG TUA TERHADAP MOTIVASI BELAJAR DARING SISWA SD PADA MASA PANDEMI COVID-19 - Reza Rezky Mubarok; Susi Erianti; Yecy Anggreny (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
The Covid-19 pandemic had an impact from various sectors, especially in the education sector which caused the learning system to be turned into an online method. Student learning motivation is impacted, when online learning students learn at home and require more attention from parents. This study aims to find out the relationship of the role of parents to the motivation of online learning of elementary students during the COVID-19 pandemic. The type of research used is quantitative using analytical correlation design through the Cross Sectional approach. The analyses used are univariate and bivariate. Bivariate analysis using the Chi Square Test. A sample of 183 people, in the form of random sampling with proportionate sratified sampling technique. Chi Square test result obtained Pvalue = 0.009 (< 0.05). The results of bivariate analysis showed that there is a relationship between the role of parents to the motivation of online learning of elementary school students during the COVID-19 pandemic. From the results of this study, parents are expected to be more accompanying, paying attention and facilitating children's learning during online learning, so that students' learning motivation is higher during the COVID-19 pandemic.